Fighting Environmental Crime in Europe and Beyond: The Role of the EU and Its Member States - Sollund, Ragnhild Aslaug; Stefes, Christoph H.; Germani, Anna Rita (Palgrave Studies in Green Criminology, 2016)
This is a unique collection arising from a major European collaboration. It provides balanced, important and interesting essays on a range of topical issues making a significant contribution to green criminology and the study of environmental harms and crimes. Nigel South, Centre for Criminology, University of Essex. Environmental crimes may originate in specific locations, but these harms do not respect geographical borders. The chapters in this wonderful anthology describe the scope and extent of environmental wrong-doing in the EU and elsewhere, and they demonstrate the power -- indeed, the necessity -- of interdisciplinary and international collaborative and cooperative responses. This collection is indispensable for those seeking diverse examples and rich analysis of the causes and consequences of and possible solutions to a range of acts and omissions that despoil the environment. Avi Brisman, MFA, JD, PhD, Associate Professor, School of Justice Studies, College of Justice and Safety This book will bring together the findings of a multi-disciplinary and international research project funded by the European Union (EU). “European Union Action to Fight Environmental Crime" (EFFACE) was a 40-month research project that included eleven European research institutions and think tanks and was led by Ecologic Institute Berlin. EFFACE assessed the impacts of environmental crime as well as effective and feasible policy options for combating it from an multidisciplinary perspective, with a focus on the EU. As part of this project, numerous instances of environmental crime within and outside of the EU were studied and are now presented in this volume. This edited collection is highly innovative in showing not only the many facets of environmental crime, but also how it should be conceptualised and the consequences. An original and rigorous study, this book will be of particular interest to policy makers and scholars of green criminology and environmental studies